Peningkatan Kinerja Berbasis Manajemen Bakat, Servant Leadership Dan Komitmen Organisasi - Marno Nugroho; Bagas Dewantoro Pamungkas Putro (JURNAL ILMIAH MANAJEMEN & BISNIS, 2021)
This study aims to analyze the effect of talent management and servant leadership on HR performance through organizational commitment. The population in this study were all employees of PSDA-ESDM Semarang. The sampling technique using purposive random sampling is a sampling technique that uses certain criteria or considerations. Samples taken were 84 respondents, with a research instrument in the form of a questionnaire. Data analysis uses multiple linear regression. The results showed that talent management had a positive and significant effect on organizational commitment, Servant leadership had a positive and significant effect on organizational commitment. Talent management has a positive and significant effect on HR performance. Servant leadership has a positive and significant effect on HR performance. Organizational commitment has a positive and significant effect on HR performance. Organizational commitment is not able to mediate the influence of talent management and servant leadership on HR performance.